Geografski prehod - Klemenčič, Marijan M. (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
The paper emphasizes the significance of geographical elements in the phase of transition from one stage of development to another, presented through a case study of demographical, economic and socioeconomic transition, family atomization, mixed worker-peasant households, contemporary fallow and urnabization. The primary stress is given to the idea of geographical transtion.
Keywords: družbena geografija; geografija; geography; human geography; pokrajina; raziskovanje; Subdivisions of the Kingdom of Yugoslavia